TouchDevelop — App Development on Mobile Devices - Tillmann, Nikolai; Moskal, Michal; Fahndrich, Manuel; Burckhardt, Sebastian; Halleux, Jonathan "Peli" de (Proc. 20th International Symposium on Foundations of Software Engineering (FSE 2012), Demonstration, 2012)
Mobile devices are becoming the prevalent computing platform for most people. TouchDevelop is a new mobile development environment that enables anyone with a Windows Phone to create new apps directly on the smartphone, without a PC or a traditional keyboard. At the core is a new mobile programming language and editor that was designed with the touchscreen as the only input device in mind. Programs written in TouchDevelop can leverage all phone sensors such as GPS, cameras, accelerometer, gyroscope, and stored personal data such as contacts, songs, pictures. Thousands of programs have already been written and published with TouchDevelop.